Digital and Sustainable Transition: Status of European Union Production of Transport Equipment Sector - Aurelija Burinskiene (Journal of Sustainable Manufacturing in Transportation, 2024)
The European Digital Decade (2030) strategy sets out guidelines for digitalisation in Europe, meaning that more than 90% of businesses have achieved at least their significant digitisation capacity. The European Commission is committed to implementing the European Green Deal to reduce its environmental impact. Production of the transport equipments sector will play an important role in Europe's green and digital transition, creating technologies that contribute to sustainable development and strengthen Europe. The limited and fragmented use of digital and sustainable technologies at the European Union level within the Production of the transport equipments sector is identified. The results of the publication show that the number of papers on digital practices is five times higher than the number of papers on sustainable practices. This article aims to develop guidelines that allow the Production of the transport equipments sector to accelerate the transition among the European Union member states.The author proposed a two-step approach to testing for the digital and sustainable transition of Production of the transport equipments sector. According to this method, the researcher of this study mainly analyzes and compares data from the European Union 27 Production of the transport equipments sectors, reflecting the performance activities among the manufacturing sector in general. The results show that 8 Production of the transport equipments sector digital and sustainable indicators are lower than the European Union average of the manufacturing sector. In addition, the proposed interdisciplinary ranking system is being developed to consider decision-making and progress in transitioning to a more digital and sustainable landscape. The study identifies areas needing more attention from Production of the transport equipments sector and policymakers and aligns the green and digital transitions.